Judicial Pardon after the New Criminal Procedure Code: Procedural Operationalization in Indonesia’s Criminal Justice Reform - Patrick Corputty; Pujiyono Pujiyono; Irma Cahyaningtyas (Faculty of Law Universitas Jenderal Soedirman, 2026)
Judicial pardon is an important innovation in Indonesia’s 2023 Criminal Code because it allows judges to declare a defendant guilty while refraining from imposing punishment or measures. This article examines judicial pardon as a form of judicial discretion oriented toward proportionality, substantive justice, and the humanization of punishment, while also analysing its procedural operationalization after the enactment of the New Criminal Procedure Code of 2025. Using doctrinal legal research with statutory, conceptual, case, and comparative approaches, this article compares analogous mechanisms in the Netherlands, England and Wales, and France. The findings show that the New Criminal Procedure Code has formally recognized judicial pardon as a distinct form of court decision and allows legal remedies against it. However, its implementation still requires clearer procedural safeguards, particularly concerning eligibility requirements, stages of examination, victim participation, the duty to give reasons, judgment format, review mechanisms, and oversight. Comparative experience shows that discretion not to impose punishment can operate effectively only when embedded in a transparent, participatory, reasoned, and reviewable procedure. This article argues that a Supreme Court Regulation, as mandated by Article 246(4) of the New Criminal Procedure Code, is necessary to operationalize judicial pardon in a fair, proportionate, accountable, and legally certain manner.